Locomotive of the White Pass & Yukon Railroad on trestle, possibly Alaska, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "White Pass and Yukon RR" Original photograph by Eric A. Hegg 615; copied by Webster and Stevens 67.A.